Preparation method of toughened alumina-based insulator material

CN122897694APending Publication Date: 2026-10-13HUNAN SUN POWER ELECTRIC PORCELAIN APPLIANCE MFG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611325684.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种增韧型氧化铝基绝缘子材料的制备方法,以解决现有碳化硅晶须增韧氧化铝陶瓷在烧结过程中晶须易与基体发生界面反应及氧化损伤的问题

Benefits of technology

(1)本发明通过预氧化处理在碳化硅晶须表面形成致密的二氧化硅层,该氧化层由碳化硅本体氧化生成,与晶须之间为化学键合,结构致密,能够阻隔氧气向晶须内部扩散,抑制高温烧结过程中晶须的进一步氧化,使碳化硅晶须的本征强度得以保留,为晶须发挥拔出和桥接增韧作用提供了强度基础,有利于提升材料的断裂韧性和抗弯强度;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of functional ceramics, in particular to a preparation method of a toughened alumina-based insulator material; the method takes alpha-alumina powder as a matrix, takes aluminum nitrate nonahydrate and tetraethyl orthosilicate as precursors, in-situ forms a composite coating layer on the surface of the matrix particles and interface modified silicon carbide whiskers through a sol-gel method, obtains coated powder through drying, calcination and grinding, and then obtains the toughened alumina-based insulator material through granulation, isostatic pressing forming, glue removal and sintering; the interface modified silicon carbide whisker is obtained through three-step surface modification treatment of the silicon carbide whisker, i.e., forming a silica inner layer through pre-oxidation, forming an alumina intermediate layer through heterogeneous precipitation and forming a rare earth aluminosilicate outer shell layer through sol-gel co-deposition; the insulator material has high fracture toughness and bending strength while guaranteeing insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional ceramics technology, specifically to a method for preparing a toughened alumina-based insulator material. Background Technology

[0002] Alumina ceramic insulators are widely used in power transmission and distribution systems due to their excellent insulation performance, good chemical stability, and high mechanical strength. With the development of ultra-high voltage (UHV) transmission technology, higher requirements have been placed on the mechanical reliability of insulators. However, the inherent brittleness of alumina ceramics makes them prone to brittle fracture under mechanical stress or thermal shock, limiting their long-term service safety under harsh conditions. To improve the fracture toughness of alumina ceramics, introducing whiskers or fibers into the matrix as toughening phases has become an important technical direction in this field. Among them, silicon carbide whiskers, with their high strength, high elastic modulus, and good high-temperature stability with the alumina matrix, are considered one of the ideal toughening materials.

[0003] In the prior art, methods for forming silicon carbide whisker-toughened alumina ceramics have been reported. Chinese patent application CN116444285A discloses an injection molding method for silicon carbide whisker-toughened alumina ceramics. This patented technology involves ball milling and mixing silicon carbide whiskers, titanium diboride, and alumina, followed by intensive mixing, injection molding, dewaxing and degreasing, and sintering to obtain the ceramic material. This method has high production efficiency, allows for control of processing allowances, and reduces production costs. However, during the atmospheric pressure sintering process of alumina ceramics, silicon carbide whiskers are prone to interfacial reactions with the alumina matrix at high temperatures. Simultaneously, the whisker surface suffers oxidative damage in an oxidizing atmosphere, leading to a decrease in the intrinsic strength of the whiskers and a weakening of the toughening effect. Furthermore, the interfacial bonding state between the whiskers and the matrix directly affects the mechanical and insulating properties of the composite material. How to effectively control the interfacial bonding between the whiskers and the alumina matrix remains a key technical problem in this field.

[0004] Therefore, how to effectively suppress the interfacial reaction and oxidation of silicon carbide whiskers during sintering, while improving the interfacial bonding state between the whiskers and the alumina matrix, and fully enhancing the fracture toughness and mechanical strength of the material while ensuring its insulation performance, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing toughened alumina-based insulator materials, so as to solve the problem that existing silicon carbide whisker-toughened alumina ceramics are prone to interfacial reactions and oxidation damage with the matrix during sintering.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a toughened alumina-based insulator material includes the following steps: S1. By weight, take 100 parts of α-alumina powder, 15-25 parts of aluminum nitrate nonahydrate, 8-15 parts of tetraethyl orthosilicate and 5-12 parts of interface-modified silicon carbide whiskers and add them to 200-300 parts of anhydrous ethanol and ultrasonically disperse them to form a slurry. Add ammonia water dropwise to the slurry to adjust the pH value to 8.5-9.5, stir the reaction, let it stand, and form a wet gel. S2. After drying the wet gel, calcin it, let it cool naturally, and then grind it through a 200-mesh sieve to obtain the coated powder; S3. Add an ethanol solution of polyvinyl butyral to the coated powder and mix by wet ball milling. After drying, granulate the powder by passing it through an 80-mesh sieve to obtain granulated powder. S4. Press the granulated powder into a shape to obtain a raw blank; S5. The raw blank is debonded in air, then sintered and cooled to room temperature to obtain toughened alumina-based insulator material.

[0007] Furthermore, the interface-modified silicon carbide whiskers are prepared by the following method: A1. Silicon carbide whiskers are heated to 850-950°C in air at a rate of 8-12°C / min and held for 1-2 hours. After cooling in the furnace, pre-oxidized silicon carbide whiskers are obtained. A2. Add pre-oxidized silicon carbide whiskers to an anhydrous ethanol solution of aluminum nitrate nonahydrate, disperse by ultrasonication, add ammonia dropwise to adjust the pH to 8.8-9.5, stir the reaction, let stand, filter and wash, dry the filter cake and calcine to obtain composite coated whiskers; A3. The composite coated whiskers are added to anhydrous ethanol, ultrasonically dispersed, and then tetraethyl orthosilicate, aluminum nitrate nonahydrate and yttrium nitrate hexahydrate are added. The mixture is stirred to obtain a suspension. Ammonia is added dropwise to the suspension to adjust the pH to 9.0-9.8. After stirring and reacting, the mixture is allowed to stand, filtered and washed. The filter cake is dried and calcined. After cooling to room temperature in the furnace, it is passed through a 200-mesh sieve to obtain the final product.

[0008] Furthermore, in step A2, the amount of pre-oxidized silicon carbide whiskers added is 8-12 parts by weight, and the amount of anhydrous ethanol solution of aluminum nitrate nonahydrate added is 80-120 parts.

[0009] Furthermore, in step A2, the calcination temperature is 500–550°C, and the calcination time is 1–2 hours.

[0010] Furthermore, in step A3, by weight, the amount of anhydrous ethanol added is 80-120 parts, the amount of tetraethyl orthosilicate added is 2-5 parts, the amount of aluminum nitrate nonahydrate added is 0.5-1.5 parts, and the amount of yttrium nitrate hexahydrate added is 0.3-0.8 parts; the calcination temperature is 550-650℃, and the calcination time is 0.5-1h.

[0011] Furthermore, in step S2, the heating rate of calcination is 3-5℃ / min, the calcination temperature is 500-600℃, and the calcination time is 1-2h.

[0012] Furthermore, in step S3, the mass concentration of the polyvinyl butyral ethanol solution is 5% to 10%, and the amount of polyvinyl butyral ethanol solution added is 30% to 60% of the total mass of the coated powder; the medium for wet ball milling is anhydrous ethanol, the ball milling speed is 200 to 300 rpm, and the ball milling time is 4 to 6 hours.

[0013] Furthermore, in step S4, the pressing and molding process uses isostatic pressing with a pressure of 150-250 MPa and a holding time of 3-5 minutes.

[0014] Furthermore, in step S5, the heating rate for glue removal is 2-4℃ / min, the glue removal temperature is 500-600℃, and the glue removal time is 1-2h.

[0015] Furthermore, in step S5, the sintering heating rate is 8–12 °C / min, the sintering temperature is 1480–1580 °C, and the sintering time is 2–4 h.

[0016] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention forms a dense silicon dioxide layer on the surface of silicon carbide whiskers through pre-oxidation treatment. The oxide layer is generated by oxidation of silicon carbide body and is chemically bonded to the whiskers. The structure is dense and can block oxygen from diffusing into the whiskers, inhibit further oxidation of the whiskers during high-temperature sintering, and retain the intrinsic strength of silicon carbide whiskers. This provides a strength basis for the whiskers to play the role of pull-out and bridging toughening, which is beneficial to improving the fracture toughness and bending strength of the material. (2) In this invention, an alumina intermediate layer is coated on the outside of the silicon dioxide layer. Since the intermediate layer has the same composition as the α-alumina matrix, the two have excellent chemical compatibility, which can reduce the interfacial energy between the whiskers and the matrix, improve the wetting effect of the matrix on the whiskers during sintering, and promote interfacial bonding. At the same time, the intermediate layer is already dense after calcination, which can block the rare earth ions in the outer shell layer from diffusing to the surface of the silicon carbide whiskers, avoid the adverse reactions that may be caused by direct contact between the two, and ensure the stability of the structure of each functional layer. (3) The outermost layer of this invention is a rare earth aluminosilicate amorphous shell layer. During the sintering heating process, the shell layer has a lower softening temperature due to its amorphous state, which can soften first to form an interfacial liquid phase micro-region. The liquid phase drives the matrix particles around the whiskers to rearrange through capillary force, promotes local densification and fills the micropores between the whiskers and the matrix. After cooling, a tight interfacial bond is formed, which allows stress to be effectively transferred from the matrix to the whiskers. At the same time, when the crack extends to the interface, the whiskers can be pulled out to consume energy, thereby improving the fracture toughness and bending strength of the material. In addition, the filling of the interfacial micropores reduces the migration channels of charge carriers along the interface, which is beneficial to maintaining a high volume resistivity. (4) In this invention, interface-modified silicon carbide whiskers and α-alumina powder are in situ composited in the liquid phase by sol-gel method. The precursor sol uniformly coats the surface of the whiskers and matrix particles, achieving uniform mixing of the two and avoiding the problem of whisker agglomeration due to van der Waals forces in traditional mechanical mixing method. After sintering, the whiskers are uniformly distributed in three dimensions in the matrix, with consistent toughening effect in all directions, and the mechanical properties of the material are stable. (5) The toughened alumina-based insulator material prepared by the present invention has high fracture toughness and bending strength while maintaining high volume resistivity, and is suitable for mass production. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1 A method for preparing a toughened alumina-based insulator material includes the following steps: S1. By weight, 100 parts of α-alumina powder with an average particle size of 0.5 μm, 15 parts of aluminum nitrate nonahydrate, 8 parts of tetraethyl orthosilicate and 5 parts of interface-modified silicon carbide whiskers were added to 200 parts of anhydrous ethanol and ultrasonically dispersed at 20 kHz frequency and 100 W power for 30 min to form a slurry. Ammonia was added dropwise to the slurry at a rate of 1 mL / min under a water bath at 60 ℃ to adjust the pH value to 8.5. The mixture was stirred at 200 rpm for 2 h and allowed to stand to form a wet gel. S2. After drying the wet gel at 100℃ for 12h, it is heated to 500℃ in air at a rate of 3℃ / min and kept at that temperature for 1h. After natural cooling, it is ground through a 200-mesh sieve to obtain the coated powder. S3. Add a 5% (w / w) polyvinyl butyral ethanol solution to the coated powder and perform wet ball milling. The medium for wet ball milling is anhydrous ethanol. The ball milling speed is 200 rpm, the ball milling time is 4 h, and the ball-to-powder ratio is 3:1. After drying at 60℃ for 2 h, granulate through an 80-mesh sieve to obtain granulated powder. The amount of polyvinyl butyral ethanol solution added is 30% of the total mass of the coated powder. S4. The granulated powder is pressed into a green body by isostatic pressing at 150MPa for 3 minutes to obtain a green body. S5. The raw blank is heated to 500℃ in air at a rate of 2℃ / min and held for 1 hour to remove the glue. Then, it is heated to 1480℃ at a rate of 8℃ / min and held for 2 hours to sinter. Finally, it is cooled to room temperature at a rate of 3℃ / min to obtain toughened alumina-based insulator material.

[0019] The interface-modified silicon carbide whiskers are prepared by the following method: A1. Silicon carbide whiskers are heated to 850°C in air at a rate of 8°C / min and held for 1 hour. After cooling in the furnace, pre-oxidized silicon carbide whiskers are obtained, wherein the diameter of the silicon carbide whiskers is 0.2 μm and the aspect ratio is 10. A2. By weight, 8 parts of pre-oxidized silicon carbide whiskers were added to 80 parts of anhydrous ethanol solution of aluminum nitrate nonahydrate with a concentration of 0.08 mol / L. After ultrasonic dispersion at 20 kHz frequency and 100 W power for 20 min, ammonia water was added dropwise at a rate of 1 mL / min to adjust the pH value to 8.8. After reacting for 2 h with stirring at 150 rpm, the mixture was allowed to stand, filtered, and washed twice with anhydrous ethanol. The filter cake was dried at 100 °C for 6 h, then calcined at 500 °C for 1 h in air atmosphere, and ground through a 200 mesh sieve to obtain composite coated whiskers. A3. The composite coated whiskers were added to 80 parts of anhydrous ethanol and ultrasonically dispersed for 20 min at 20 kHz frequency and 100 W power. Then, 2 parts of tetraethyl orthosilicate, 0.5 parts of aluminum nitrate nonahydrate and 0.3 parts of yttrium nitrate hexahydrate were added. A suspension was obtained by stirring at 150 rpm. Ammonia was added dropwise to the suspension at a rate of 1 mL / min to adjust the pH to 9.0. After stirring for 3 h, the mixture was allowed to stand for 1 h. The mixture was filtered and washed twice with anhydrous ethanol. The filter cake was dried at 80 °C for 6 h and then calcined at 550 °C for 0.5 h in air. After cooling to room temperature in the furnace, the mixture was passed through a 200-mesh sieve to obtain the final product.

[0020] Example 2 A method for preparing a toughened alumina-based insulator material includes the following steps: S1. By weight, 100 parts of α-alumina powder with an average particle size of 1.5 μm, 20 parts of aluminum nitrate nonahydrate, 12 parts of tetraethyl orthosilicate and 8 parts of interface-modified silicon carbide whiskers were added to 250 parts of anhydrous ethanol and ultrasonically dispersed at 30 kHz frequency and 200 W power for 45 min to form a slurry. Ammonia was added dropwise to the slurry at a rate of 2 mL / min under a water bath at 70 ℃ to adjust the pH value to 9.0. The mixture was stirred at 300 rpm for 3 h and allowed to stand to form a wet gel. S2. After drying the wet gel at 110℃ for 18h, it is heated to 550℃ in air at a rate of 4℃ / min and kept at that temperature for 1.5h. After natural cooling, it is ground through a 200-mesh sieve to obtain the coated powder. S3. Add an 8% (w / w) polyvinyl butyral ethanol solution to the coated powder and perform wet ball milling. The medium for wet ball milling is anhydrous ethanol. The ball milling speed is 250 rpm, the ball milling time is 5 h, and the ball-to-powder ratio is 4:1. After drying at 70℃ for 3 h, granulate through an 80-mesh sieve to obtain granulated powder. The amount of polyvinyl butyral ethanol solution added is 45% of the total mass of the coated powder. S4. The granulated powder is pressed into a green body by isostatic pressing at 200MPa for 4 minutes to obtain a green body. S5. The raw blank is heated to 550℃ in air at a rate of 3℃ / min and held for 1.5h for debinding. Then it is heated to 1530℃ at a rate of 10℃ / min and held for sintering for 3h. Finally, it is cooled to room temperature at a rate of 4℃ / min to obtain toughened alumina-based insulator material.

[0021] The interface-modified silicon carbide whiskers are prepared by the following method: A1. Silicon carbide whiskers are heated to 900°C in air at a rate of 10°C / min and held for 1.5 hours. After cooling in the furnace, pre-oxidized silicon carbide whiskers are obtained, wherein the diameter of the silicon carbide whiskers is 0.6 μm and the aspect ratio is 20. A2. By weight, 10 parts of pre-oxidized silicon carbide whiskers were added to 100 parts of anhydrous ethanol solution of aluminum nitrate nonahydrate with a concentration of 0.12 mol / L. After ultrasonic dispersion at 30 kHz frequency and 200 W power for 30 min, ammonia water was added dropwise at a rate of 2 mL / min to adjust the pH value to 9.2. After reacting for 2.5 h with stirring at 200 rpm, the mixture was allowed to stand, filtered, and washed three times with anhydrous ethanol. The filter cake was dried at 110 °C for 9 h, then calcined at 520 °C in air for 1.5 h. After grinding through a 200 mesh sieve, composite coated whiskers were obtained. A3. The composite coated whiskers were added to 100 parts of anhydrous ethanol and ultrasonically dispersed at 30kHz frequency and 200W power for 30min. Then, 3 parts of tetraethyl orthosilicate, 1.0 part of aluminum nitrate nonahydrate and 0.5 parts of yttrium nitrate hexahydrate were added. A suspension was obtained by stirring at 200rpm. Ammonia was added dropwise to the suspension at a rate of 2mL / min to adjust the pH to 9.4. After stirring for 4h, the mixture was allowed to stand for 1.5h, filtered and washed 3 times with anhydrous ethanol. The filter cake was dried at 90℃ for 9h and then calcined at 600℃ in air for 0.8h. After cooling to room temperature in the furnace, the mixture was passed through a 200-mesh sieve to obtain the final product.

[0022] Example 3 A method for preparing a toughened alumina-based insulator material includes the following steps: S1. By weight, 100 parts of α-alumina powder with an average particle size of 3μm, 25 parts of aluminum nitrate nonahydrate, 15 parts of tetraethyl orthosilicate and 12 parts of interface-modified silicon carbide whiskers were added to 300 parts of anhydrous ethanol and ultrasonically dispersed at 40kHz frequency and 300W power for 60min to form a slurry. Ammonia was added dropwise to the slurry at a rate of 3mL / min under water bath conditions at 80℃ to adjust the pH value to 9.5. The mixture was stirred at 400rpm for 4h and allowed to stand to form a wet gel. S2. After drying the wet gel at 120℃ for 24h, it is heated to 600℃ in air at a rate of 5℃ / min and kept at that temperature for 2h. After natural cooling, it is ground through a 200-mesh sieve to obtain the coated powder. S3. Add a 10% (w / w) polyvinyl butyral ethanol solution to the coated powder and perform wet ball milling and mixing. The medium for wet ball milling is anhydrous ethanol. The ball milling speed is 300 rpm, the ball milling time is 6 h, and the ball-to-powder ratio is 5:1. After drying at 80℃ for 4 h, granulate through an 80-mesh sieve to obtain granulated powder. The amount of polyvinyl butyral ethanol solution added is 60% of the total mass of the coated powder. S4. The granulated powder is pressed into a green body by isostatic pressing at 250MPa for 5 minutes to obtain a green body. S5. The raw blank is heated to 600℃ in air at a rate of 4℃ / min and held for 2 hours to remove the glue. Then, it is heated to 1580℃ at a rate of 12℃ / min and held for 4 hours to sinter. Finally, it is cooled to room temperature at a rate of 5℃ / min to obtain toughened alumina-based insulator material.

[0023] The interface-modified silicon carbide whiskers are prepared by the following method: A1. Silicon carbide whiskers are heated to 950°C in air at a rate of 12°C / min and held for 2 hours. After cooling in the furnace, pre-oxidized silicon carbide whiskers are obtained, wherein the diameter of the silicon carbide whiskers is 1.0 μm and the aspect ratio is 30. A2. By weight, 12 parts of pre-oxidized silicon carbide whiskers were added to 120 parts of anhydrous ethanol solution of aluminum nitrate nonahydrate with a concentration of 0.15 mol / L. After ultrasonic dispersion at 40 kHz frequency and 300 W power for 40 min, ammonia water was added dropwise at a rate of 3 mL / min to adjust the pH value to 9.5. After reacting for 3 h with stirring at 300 rpm, the mixture was allowed to stand, filtered, and washed 4 times with anhydrous ethanol. The filter cake was dried at 120 °C for 12 h, then calcined at 550 °C for 2 h in air atmosphere, and ground through a 200 mesh sieve to obtain composite coated whiskers. A3. The composite coated whiskers were added to 120 parts of anhydrous ethanol and ultrasonically dispersed at 40kHz frequency and 300W power for 40min. Then, 5 parts of tetraethyl orthosilicate, 1.5 parts of aluminum nitrate nonahydrate and 0.8 parts of yttrium nitrate hexahydrate were added. A suspension was obtained by stirring at 300rpm. Ammonia was added dropwise to the suspension at a rate of 3mL / min to adjust the pH to 9.8. The mixture was stirred for 5h and then allowed to stand for 2h. The mixture was filtered and washed 4 times with anhydrous ethanol. The filter cake was dried at 100℃ for 12h and then calcined at 650℃ in air for 1h. After cooling to room temperature in the furnace, the mixture was passed through a 200-mesh sieve to obtain the final product.

[0024] Comparative Example 1 The main difference between this comparative example and Example 1 is that an equal amount of silicon carbide whiskers are used in this comparative example instead of interface-modified silicon carbide whiskers, while the other components and preparation methods are completely consistent with Example 1.

[0025] Comparative Example 2 The main difference between this comparative example and Example 1 is that an equal amount of pre-oxidized silicon carbide whiskers are used instead of interface-modified silicon carbide whiskers in this comparative example, while the other components and preparation methods are completely consistent with Example 1.

[0026] Comparative Example 3 The main difference between this comparative example and Example 1 is that an equal amount of composite coated whiskers are used in this comparative example instead of interface-modified silicon carbide whiskers, while the other components and preparation methods are completely consistent with Example 1.

[0027] Performance testing: The insulator materials obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to the following relevant performance tests, and the test results are shown in Table 1: (1) Bending strength: The test shall be conducted in accordance with the provisions of GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics". The three-point bending method shall be adopted, the span shall be 30 mm, the loading rate shall be 0.5 mm / min, the maximum bending stress shall be recorded after the specimen breaks, and the bending strength shall be calculated. (2) Fracture toughness: The test shall be conducted in accordance with the provisions of GB / T 23806-2025 "Test Method for Fracture Toughness of Fine Ceramics - Single-sided Precracked Beam (SEPB) Method". The single-sided precracked beam method shall be adopted, the ratio of the specimen notch depth to the specimen height shall be 0.5, the span shall be 30 mm, and the loading rate shall be 0.05 mm / min. (3) Volume resistivity: A three-electrode system was used, and the test temperature was room temperature for 15 minutes. A DC voltage of 500V was applied, and the volume resistivity value R was read after 1 minute. v According to ρ v =0.785· Calculate the volume resistivity, where ρ v R is the volume resistivity (Ω·cm). v d is the volume resistivity (Ω), d is the diameter of the measuring electrode (cm), and t is the sample thickness (cm). (4) Relative density: The Archimedes displacement method was used, with distilled water as the impregnation medium. After the sample was dried to constant weight, the dry weight m1 was measured. After vacuum impregnation to saturation, the wet weight m2 was measured. The apparent mass m3 of the saturated sample was measured by the suspension method. The bulk density ρ was calculated. b relative density ×100%, where ρ th For theoretical density, This is the density of distilled water.

[0028] Table 1 Example 1 486.3 5.7 5.9 97.3 Example 2 531.7 6.6 7.4 98.6 Example 3 518.4 6.3 7.1 98.3 Comparative Example 1 372.5 4.1 1.3 93.8 Comparative Example 2 428.6 4.7 2.2 95.2 Comparative Example 3 449.1 5.2 4.6 96.5 As can be seen from the test results in Table 1, the bending strength, fracture toughness, volume resistivity, and relative density of the examples are all superior to those of the comparative examples. Comparative Example 1 uses unmodified silicon carbide whiskers. During sintering, the whiskers are in direct contact with the α-alumina matrix, and an interfacial reaction and oxidation occur at high temperatures, resulting in damaged whisker strength and weakened toughening effect. At the same time, the interfacial defects become channels for carrier migration, leading to a decrease in insulation performance. Comparative Example 2 uses silicon carbide whiskers that have only undergone pre-oxidation treatment. Its surface has only a single layer of silica coating. Although this can inhibit whisker oxidation, the lack of the chemical compatibility transition effect of the alumina intermediate layer and the interfacial liquid phase sintering aid effect of the outer shell layer results in weak interfacial bonding between the whiskers and the α-alumina matrix, limiting the performance improvement. Comparative Example 3 uses composite coated whiskers with an inner silica layer and an alumina intermediate layer on its surface, which can effectively protect the whisker body. However, due to the lack of a rare earth aluminosilicate outer shell layer, an interfacial liquid phase micro-region cannot be formed around the whiskers during the sintering stage, resulting in a lower degree of local densification and improved interfacial bonding compared to the examples.

[0029] This invention utilizes a pre-oxidation process to form a silica inner layer, a heterogeneous precipitation process to form an alumina intermediate layer, and a sol-gel co-deposition process to form a rare-earth aluminosilicate outer shell, thereby synergistically regulating the interfacial bonding state between whiskers and the α-alumina matrix. This demonstrates that the toughened alumina-based insulator material prepared by this invention can significantly improve fracture toughness and flexural strength while maintaining insulation performance.

[0030] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0031] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a toughened alumina-based insulator material, characterized in that, Includes the following steps: S1. By weight, take 100 parts of α-alumina powder, 15-25 parts of aluminum nitrate nonahydrate, 8-15 parts of tetraethyl orthosilicate and 5-12 parts of interface-modified silicon carbide whiskers and add them to 200-300 parts of anhydrous ethanol and ultrasonically disperse them to form a slurry. Add ammonia water dropwise to the slurry to adjust the pH value to 8.5-9.5, stir the reaction, let it stand, and form a wet gel. S2. After drying the wet gel, calcin it, let it cool naturally, and then grind it through a 200-mesh sieve to obtain the coated powder; S3. Add an ethanol solution of polyvinyl butyral to the coated powder and mix by wet ball milling. After drying, granulate the powder by passing it through an 80-mesh sieve to obtain granulated powder. S4. Press the granulated powder into a shape to obtain a raw blank; S5. The raw blank is debonded in air, then sintered and cooled to room temperature to obtain toughened alumina-based insulator material.

2. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, The interface-modified silicon carbide whiskers are prepared by the following method: A1. Silicon carbide whiskers are heated to 850-950°C in air at a rate of 8-12°C / min and held for 1-2 hours. After cooling in the furnace, pre-oxidized silicon carbide whiskers are obtained. A2. Add pre-oxidized silicon carbide whiskers to an anhydrous ethanol solution of aluminum nitrate nonahydrate, disperse by ultrasonication, add ammonia dropwise to adjust the pH to 8.8-9.5, stir the reaction, let stand, filter and wash, dry the filter cake and calcine to obtain composite coated whiskers; A3. The composite coated whiskers are added to anhydrous ethanol, ultrasonically dispersed, and then tetraethyl orthosilicate, aluminum nitrate nonahydrate and yttrium nitrate hexahydrate are added. The mixture is stirred to obtain a suspension. Ammonia is added dropwise to the suspension to adjust the pH to 9.0-9.

8. After stirring and reacting, the mixture is allowed to stand, filtered and washed. The filter cake is dried and calcined. After cooling to room temperature in the furnace, it is passed through a 200-mesh sieve to obtain the final product.

3. The method for preparing the toughened alumina-based insulator material according to claim 2, characterized in that, In step A2, the amount of pre-oxidized silicon carbide whiskers added is 8-12 parts by weight, and the amount of anhydrous ethanol solution of aluminum nitrate nonahydrate added is 80-120 parts.

4. The method for preparing the toughened alumina-based insulator material according to claim 2, characterized in that, In step A2, the calcination temperature is 500–550°C and the calcination time is 1–2 hours.

5. The method for preparing the toughened alumina-based insulator material according to claim 2, characterized in that, In step A3, by weight, the amount of anhydrous ethanol added is 80-120 parts, the amount of tetraethyl orthosilicate added is 2-5 parts, the amount of aluminum nitrate nonahydrate added is 0.5-1.5 parts, and the amount of yttrium nitrate hexahydrate added is 0.3-0.8 parts; the calcination temperature is 550-650℃, and the calcination time is 0.5-1h.

6. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, In step S2, the heating rate of calcination is 3-5℃ / min, the calcination temperature is 500-600℃, and the calcination time is 1-2h.

7. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, In step S3, the mass concentration of the polyvinyl butyral ethanol solution is 5% to 10%, and the amount of polyvinyl butyral ethanol solution added is 30% to 60% of the total mass of the coated powder; the medium for wet ball milling is anhydrous ethanol, the ball milling speed is 200 to 300 rpm, and the ball milling time is 4 to 6 hours.

8. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, In step S4, isostatic pressing is used for molding, with a pressure of 150-250 MPa and a holding time of 3-5 minutes.

9. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, In step S5, the heating rate for discharging adhesive is 2-4℃ / min, the discharging temperature is 500-600℃, and the discharging time is 1-2h.

10. The method for preparing the toughened alumina-based insulator material according to claim 1, characterized in that, In step S5, the sintering heating rate is 8-12℃ / min, the sintering temperature is 1480-1580℃, and the sintering time is 2-4h.

Citation Information

Patent Citations

  • Injection molding method of silicon carbide whisker toughened aluminum oxide ceramic

    CN116444285A